2005
DOI: 10.3201/eid1109.040712
|View full text |Cite
|
Sign up to set email alerts
|

Dead Crow Density and West Nile Virus Monitoring, New York

Abstract: Persons in counties with high dead crow densities had elevated risk for disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…A study modeling dead crow densities at the county level in New York state determined that human cases were more likely to occur in counties with reported dead crow densities Ն0.1 per square mile (Eidson et al 2001a, Eidson et al 2005. These analyses were applied retrospectively and at the county-level scale (Eidson et al 2001a, Eidson et al 2005, Reisen et al 2006a; however, Þner geographic resolution would better suit community-level intervention methodologies (Julian et al 2002, Johnson et al 2006). These studies implied that crow death was associated with mosquito infection; however, few research projects have attempted to verify this relationship.…”
mentioning
confidence: 99%
“…A study modeling dead crow densities at the county level in New York state determined that human cases were more likely to occur in counties with reported dead crow densities Ն0.1 per square mile (Eidson et al 2001a, Eidson et al 2005. These analyses were applied retrospectively and at the county-level scale (Eidson et al 2001a, Eidson et al 2005, Reisen et al 2006a; however, Þner geographic resolution would better suit community-level intervention methodologies (Julian et al 2002, Johnson et al 2006). These studies implied that crow death was associated with mosquito infection; however, few research projects have attempted to verify this relationship.…”
mentioning
confidence: 99%
“…Studies in New York State revealed a positive association between county-level dead crow density (number/square mile) and the number of human cases for the years (Eidson et al 2001bJulian et al 2002;Eidson et al 2005). These studies indicate that dead crow density may provide a viable proxy for WNV activity, although the strength of associations vary by year, and are likely influenced by the prevalence of infection and the availability of remaining live crows to become infected .…”
Section: West Nile Virus: a Case Study In Surveillancementioning
confidence: 88%
“…The high susceptibility of some North American bird species for fatal WNV infection and the fact that bird mortality typically precedes human or equine WNV infection has made dead bird surveillance a focus of particular interest. Several papers evaluating the efficacy of dead bird surveillance (Eidson 2001, Eidson et al 2005, Guptill et al 2003, Mostashari et al 2003, Blackmore et al 2003, Watson et al 2004) suggested that dead bird counts are in fact predictive of subsequent local human WNV illness. However, a recent report by Brownstein et al (2004) concluded that mosquito surveillance is superior to dead bird surveillance as a basis for human WNV risk prediction and some have called for abandoning dead bird surveillance as a primary tool of WNV surveillance (NCDENR 2004).…”
Section: Introduction S Ince the Introduction Of West Nile Virusmentioning
confidence: 99%